Metabolomic Analysis, Fast Isolation of Phenolic Compounds, and Evaluation of Biological Activities of the Bark From Weinmannia trichosperma Cav. (Cunoniaceae) - Ruth Barrientos; Carlos Fernández-Galleguillos; Edgar Pastene; Mario Simirgiotis; Javier Romero-Parra; Shakeel Ahmed; Javier Echeverría (Frontiers Media S.A., 2020)
Weinmannia trichosperma Cav. (Cunoniaceae) (local name, tineo; Mapuche names, madén, mëdehue) is an endemic species of Chile and Argentina used in Mapuche traditional medicine in the treatment of chronic diarrhea, inflammation, and wound healing. This study focused on the isolation, analysis, and characterization of the biological activity of compounds and bark extracts from this plant for the first time. The infusion and tincture of the bark were characterized regarding antioxidant and important enzyme inhibitory activities, phenolics, and flavonoids content and UHPLC-ESI-OT-MS metabolite profiling. Twenty-five metabolites were detected in the medicinal infusion of W. trichosperma, three flavonols were isolated: isoastilbin, neoisoastilbin, and neoastilbin ((2R,3S)-, (2S,3R)-, and (2S,3S)-dihydroquercetin 3-O-alpha-l-rhamnoside) by countercurrent chromatography, and the isomers were quantified in the bark using a validated analytical HPLC methodology. The antioxidant properties were measured by ABTS, DPPH, FRAP, ORAC, and TEAC methods. The infusion displayed a strong DPPH and ABTS scavenging activity (IC50 = 20.58 and 3.070 µg ml−1, respectively) while a moderated effect was observed in the FRAP, ORAC, and ABTS assays. The infusion showed a content of phenolic and flavonoid compounds of 442.1 mg GAE g−1 and 15.54 mg QE g−1, respectively. Furthermore, the infusion showed a good and promissory inhibitory activity (33.80%, 33.12%, and 82.86% for AChE, BuChE, and 5-hLOX, respectively) and isoastilbin (51.70%, 50.10%, and 34.29-80.71% for AChE, BuChE, and 5-hLOX, respectively). The biomolecules identified in this study support the traditional uses of this bark and the potential industrial interest from this Valdivian plant species.